The Effect Of Return On Equity, Inventory Turnover And Gross Profit Margin On Profit Growth In Large Trading Sub-Sector Companies Listed On The Indonesia Stock Exchange 2020-2024 - Fitria Ramadhani; Ima Andriyani; Liliana Liliana; Muhni Pamuji (Universitas Dehasen Bengkulu, 2026)
The objective of this research is to determine the impact of ROE, ITO, and GPM on Indonesia Stock Exchange-listed wholesale trade subsector companies from 2020 to 2024. This quantitative study makes use of secondary data culled from publicly available company financial records. The data analysis approach utilizes multiple linear regression analysis, which is implemented in SPSS Version 26 for Windows. Hypothesis testing makes use of partial tests, simultaneous tests, correlation coefficients, and classical assumption tests, among others. Find out how return on equity, inventory turnover, and gross profit margin affect profit growth in wholesale trade subsector enterprises listed on the Indonesia Stock Exchange using simultaneous testing. Partial testing found that among the factors influencing Profit Growth in the wholesale trade subsector of firms listed on the Indonesia Stock Exchange, Return on Equity, Inventory Turnover, and Gross Profit Margin were partially significant. This indicates that the ability of the organization to control profit margins, optimize inventory turnover, and use capital effectively is a critical component in fostering profit growth. Management and investors may use profitability and activity ratios as a basis for decision-making when evaluating financial performance, according to the study.